Collateral Impact of the Coronavirus Disease 2019 (COVID-19) Pandemic on Tuberculosis Control in Jiangsu Province, China. (28th August 2020) - Liu, Qiao; Lu, Peng; Shen, Ye; Li, Changwei; Wang, Jianming; Zhu, Limei; Lu, Wei; Martinez, Leonardo
Abstract: The coronavirus disease 2019 (COVID-19) pandemic may impede global tuberculosis elimination goals. In Jiangsu Province, China, tuberculosis notifications dropped 52% in 2020 compared to 2015–2019. Treatment completion and screening for drug resistance decreased continuously in 2020. Urgent attention must be paid to tuberculosis control efforts during and after the COVID-19 pandemic.